Building a Program Verifier - Leino, Rustan; Qadeer, Shaz (Guest lecture, Shaz Qadeer's cse599f, Formal Verification of Computer Systems, University of Washington, Seattle, WA, 2006)
Spec# research goals Build the best such system we can build today Experiment with the system to get a feel for what it is like to use Advance the state of the art